2021
DOI: 10.14740/jmc3702
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib-Induced Unilateral Diffuse Alveolar Hemorrhage in a Patient With Pulmonary Adenocarcinoma

Abstract: A 70-year-old man with lung adenocarcinoma was admitted to our hospital due to progressive dyspnea, 4 months after osimertinib initiation. His chest radiograph and computed tomography revealed ground-glass opacities and consolidations dominantly in the upper left lung. He took neither antiplatelet nor anticoagulation agent. No abnormality in coagulation was detected. Bronchoalveolar lavage fluid (BALF) became serially and increasingly hemorrhagic, and confirmed the diagnosis of alveolar hemorrhage. After stero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Osimertinib‐induced pneumonitis, an adverse event, is rarely serious or fatal. Previous studies have reported GGO‐type pneumonitis, and a case study has discussed small nodule‐type pneumonitis 2–5 . However, there are no reports of nodule‐type pneumonitis mimicking lung abscess or tumor recurrence on chest CT scan, identified as osimertinib‐induced lung pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Osimertinib‐induced pneumonitis, an adverse event, is rarely serious or fatal. Previous studies have reported GGO‐type pneumonitis, and a case study has discussed small nodule‐type pneumonitis 2–5 . However, there are no reports of nodule‐type pneumonitis mimicking lung abscess or tumor recurrence on chest CT scan, identified as osimertinib‐induced lung pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported GGO‐type pneumonitis, and a case study has discussed small nodule‐type pneumonitis. 2 , 3 , 4 , 5 However, there are no reports of nodule‐type pneumonitis mimicking lung abscess or tumor recurrence on chest CT scan, identified as osimertinib‐induced lung pneumonitis. Interestingly, osimertinib rechallenge by administering both osimertinib and low‐dose prednisolone was successful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, to date, no studies have been reported in which Osimertinib was associated with gastrointestinal bleeding. [10][11][12] The only drugs used for gastrointestinal bleeding associated with EGFR-TKI were Erlotinib and gefitinib. 13 Here we report a case of advanced NSCLC with diffuse colonic mucosal bleeding detected by colonoscopy after 1.5 years of Osimertinib treatment.…”
Section: Introductionmentioning
confidence: 99%